Education Shift During COVID-19: Students’ Satisfaction with Emergency Distance Learning (International Journal of Nursing Education, 2021)
Background: COVID-19 pandemic, a global issue, enforced education system to shift with distance learningmode. This study assessed students’ satisfaction with emergency distance learning.Methods: A cross-sectional survey was done among 200 nursing students studying in five nursing campusesof Tribhuvan University. To collect data, questionnaires containing 28 statements measuring students’satisfaction with online learning on a five-point scale was used. The electronic link of the questionnaire wasshared to the participants via their emails, vibers and messengers. Descriptive analysis of data was doneusing SPSS software.Finding and Conclusion: Distance learning classes were taken through Zoom, Microsoft team, email, viberand messenger. Only 49% students were enjoying online platform applications and >90% of them felt needfor training regarding use of technology for distance learning. The learning environment was comfortablefor >2/3rd of the students, 74.5% were satisfied with the instructor’s encouragement for active learning and>1/3rd had issues with the instructor’s pace of punctuality. The classes were interrupted due to technologicalerror. The internet charges were expensive and students refused practical classes through distance learningmode.
Keywords: Distance Learning, nursing education, remote education, satisfaction, student